Implementasi Peran Kepolisian Dalam Penyelesaian Perkara Tindak Pidana Melalui Keadilan Restoratif (Studi Kasus Di Kepolisian Sektor Benteng) - Soni Putra Anni Muhara; Vivi Arfiani Siregar; Kms Novyar Satriawan (Indragiri Law Review, 2026)
The resolution of criminal cases through a restorative justice approach represents one of the breakthroughs in Indonesia's criminal justice system, emphasizing the restoration of relationships between perpetrators, victims, and the community rather than punishment alone, as regulated under Police Regulation Number 8 of 2021 concerning the Handling of Criminal Cases Based on Restorative Justice, yet its implementation at the sector-level police remains constrained by various challenges related to officers' understanding, application mechanisms, and local social factors, including within the jurisdiction of Benteng Sector Police. This study aims to examine the implementation of the police's role in resolving criminal cases through the restorative justice approach at Benteng Sector Police and to identify the obstacles encountered in its implementation, with the problem formulations being how the police's role in resolving criminal cases through restorative justice is implemented at Benteng Sector Police and what obstacles are encountered in its implementation. This study employs a sociological (empirical juridical) legal research method with a descriptive qualitative approach, where data were collected through field studies, including interviews with investigators and parties involved in the case resolution process at Benteng Sector Police, as well as literature studies on relevant laws and regulations, particularly Police Regulation Number 8 of 2021 and the Indonesian Criminal Procedure Code. The findings indicate that the implementation of the police's role in resolving criminal cases through restorative justice at Benteng Sector Police has been carried out but has not been optimally implemented, attributed to officers' limited understanding of the requirements and mechanisms of restorative justice, insufficient public socialization, inadequate mediation facilities, and uneven acceptance of settlement agreements by both parties, so that enhancing investigators' capacity, strengthening public socialization, and optimizing mediation mechanisms are necessary to effectively support the implementation of restorative justice within the jurisdiction of Benteng Sector Police.